ChemInform Abstract: A Family of Low Molecular‐Weight, Organic Catalysts for Reductive C—C Bond Formation. Issue 1 (17th December 2015) - Shaaban, Saad; Jolit, Anais; Petkova, Desislava; Maulide, Nuno
Abstract: 4‐Aminomorpholine is established as a versatile catalyst for the 2‐arylation of 5‐membered heterocycles, the α‐arylation of aryl and alkyl ketone derivatives as well as the arylation of quinone which are each performed using aryldiazonium salts as the arene source.